2012
DOI: 10.1007/s10753-012-9532-8
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory and Anti-inflammatory Effect of p-Coumaric Acid, a Common Dietary Polyphenol on Experimental Inflammation in Rats

Abstract: In this study, p-coumaric acid was evaluated for its immunomodulatory and anti-inflammatory properties in vivo. The immunomodulatory effect of p-coumaric acid (100 mg/kg body weight) was assessed by evaluating its effect on cell-mediated immune responses (delayed type hypersensitivity reaction), serum immunoglobulin levels, and macrophage phagocytic index in rats. The anti-inflammatory effects of p-coumaric acid (100 mg/kg body weight) were investigated by examining its effect on expression of tumor necrosis f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
102
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(118 citation statements)
references
References 24 publications
5
102
0
1
Order By: Relevance
“…Tricaffeoylquinic acid seems to attenuate TNF-Į-stimulated inflammatory mediators production by keratinocytes, suppressing the activation of Akt and NF-țB pathways which may be mediated by reactive oxygen species, suggesting that this compound may exert inhibitory effects against the pro-inflammatory mediator-induced skin disease (Lee et al, 2011). Another active component present in the propolis (pcoumaric acid) showed anti-inflammatory effects in adjuvant-induced arthritic rats by decreasing TNF-Į expression (Pragasam et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Tricaffeoylquinic acid seems to attenuate TNF-Į-stimulated inflammatory mediators production by keratinocytes, suppressing the activation of Akt and NF-țB pathways which may be mediated by reactive oxygen species, suggesting that this compound may exert inhibitory effects against the pro-inflammatory mediator-induced skin disease (Lee et al, 2011). Another active component present in the propolis (pcoumaric acid) showed anti-inflammatory effects in adjuvant-induced arthritic rats by decreasing TNF-Į expression (Pragasam et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Later Kim et al (2006) reported potentials of gallic acid to down-regulate pro-inflammatory cytokines such as TNF-a and IL-6 in mast cells. The dietary phenol PCA increases immunoglobulin levels and decreases TNF-a levels in vivo (Pragasam et al 2013), in addition, it inhibits thromboxane B 2 production and LPS-induced PGE 2 generation in vitro (Luceri et al 2007). MY has demonstrated anti-inflammatory activity under xyleneinduced ear edema, acetic acid-induced vascular permeability, carrageenan-induced paw edema, leukocyte migration, and cotton pellet granuloma models (Wang et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ferulic acid has wound healing activity via enhancement of oxidative defense (heme oxygenase-1 and heat shock protein-70) and suppression of protein and lipid oxidation in vitro in human dermal fibroblasts (Calabrese et al, 2008). Furthermore, -coumaric acid showed anti-inflammatory function via reduction of cell-mediated immune responses, macrophage phagocyte function and TNF-a expression (Pragasam et al, 2013).…”
Section: Discussionmentioning
confidence: 99%